2021
DOI: 10.3390/children8090790
|View full text |Cite
|
Sign up to set email alerts
|

Transient Congenital Complete Heart Block: A Case Report

Abstract: Congenital complete heart block is defined as a complete atrioventricular block occurring prenatally, at birth, or within the first month of life. Congenital complete heart block has a high mortality rate, and in infants with normal heart morphology, it is often associated with maternal connective tissue disease. In these latter cases, neonatal congenital complete heart block is usually irreversible. We present a rare case of a female neonate who had bradycardia noted at a gestational age of 37 weeks. Her moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…A few case reports in the literature demonstrated a spontaneous recovery of advanced heart block without treatment. One case report involved an infant who had a complete congenital heart block in the third trimester spontaneously reverting to a normal sinus rhythm 5 days after birth without intervention or medication [ 27 ] . Kitazawa et al reported a case of advanced atrioventricular block in the patient without any comorbidities after gynaecological surgery that may have been triggered by postoperative nausea, with spontaneous recovery [ 28 ] .…”
Section: Discussionmentioning
confidence: 99%
“…A few case reports in the literature demonstrated a spontaneous recovery of advanced heart block without treatment. One case report involved an infant who had a complete congenital heart block in the third trimester spontaneously reverting to a normal sinus rhythm 5 days after birth without intervention or medication [ 27 ] . Kitazawa et al reported a case of advanced atrioventricular block in the patient without any comorbidities after gynaecological surgery that may have been triggered by postoperative nausea, with spontaneous recovery [ 28 ] .…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, the indication for pacing has widened, and it is estimated that 65%-90% of CCHB patients are treated with a pacemaker[ 17 ]. Of chief concern, pacemaker implantation is not a risk-free procedure, and fracture, repeated battery replacement, infection, and particularly pacemaker-induced heart failure are stubborn issues[ 18 - 20 ]. Over the years, pacing strategies have evolved from traditional right ventricular pacing to cardiac resynchronization therapy and, more recently, to the introduction of epicardial pacing and His bundle pacing because of their potential benefits in mitigating ventricular dys-synchrony and mechanical adverse remodeling[ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Congenital complete heart block (CCHB) is an abnormality of the cardiac impulse conduction system diagnosed on or before 28 days of life. 1 It has an incidence of 1 in 15,000–22,000 live births. 1 It is found to be associated with passive maternal autoimmune disease in 50% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…1 It has an incidence of 1 in 15,000–22,000 live births. 1 It is found to be associated with passive maternal autoimmune disease in 50% of cases. 2 Neonatal lupus erythematosus (NLE) is one such disease that typically presents with transient skin rash, cardiac involvement in the form of cardiac conduction disturbances, hepatobiliary, haematological, pulmonary and neurological abnormalities.…”
Section: Introductionmentioning
confidence: 99%